Possible applications of gliptins (dipeptidyl peptidase-4 inhibitors) in patients with type 2 diabetes mellitus on the various modes of insulin therapy - Gagik Radikovich Galstyan; Svetlana Viktorovna Sergeeva (Сахарный диабет)
The evidence for DPP-4 inhibitors effectiveness at the late stages of type 2 diabetes mellitus (T2DM) are still growing. This is particularly important for those patients who receive insulin without adequately glycemic control. This publication provides the overview of studies which demonstrate high efficacy of Vildagliptin in reducing the blood glucose level in patients with hight duration of T2DM and insulin therapy. DPP-4 inhibitors normalize basal and postprandial glucagon secretion with pancreas α-cells that helps to provide better glycemic control and to reduce a risk of hypoglycemia. Besides, there are very interesting data for Vildagliptin to reduce insulin requirement in T2DM patients in addition to HbA1clevel decrease.